UPAYA PENINGKATAN LITERASI BERBICARA MELALUI MODEL PEMBELAJARAN BERDIFERENSIASI PADA SISWA SD UNISMUH MAKASSAR - Ulviani, Maria; Arisa; Rosmalina Kemala; Akbar Aba (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This classroom action research aims to improve students’ speaking literacy through the application of differentiated instruction in SD Unismuh Makassar. The background of the problem stems from the students’ low speaking participation and limited vocabulary in expressing their thoughts verbally. The objective of the research is to enhance students’ ability to speak coherently and confidently in learning activities. The study was conducted in two cycles, with each cycle including planning, action, observation, and reflection stages. The subjects of the study were fourth-grade students, and the data collection techniques included observation, field notes, and speaking performance assessments. The results showed a significant improvement in students’ speaking skills in terms of fluency, clarity, and confidence. The differentiated learning model, which accommodated students’ needs, readiness, and interests, effectively created an inclusive and engaging learning atmosphere. It also supported teachers in designing more adaptive strategies. Based on the findings, differentiated instruction is recommended as an effective alternative method to foster speaking literacy in elementary school settings.